A Comparative Study on Vertical Dynamic Responses of Three Types of Elevated Railway Tracks Subjected to a Moving Train. (25th August 2019) - Shi, Li; Ye, Xiaoqiang; Zhang, Pengfei; Guo, Lin
Abstract : A theoretical model incorporating the moving train, the railway track, and the elevated viaduct is established and then solved using periodic theory in this paper. The vertical wheel/rail forces and the dynamic responses of track and viaduct girder are obtained and compared for three different types of tracks, i.e., the double-block ballastless track, the rubber-pad floating slab track, and the steel-spring floating slab track. It is observed that the rubber-pad and steel-spring floating slab tracks can reduce more than 10% of the wheel/rail force and the reaction force at girder supports, when compared to those of the double-block ballastless track. Especially, the steel-spring floating slab track develops an uplifting force larger than the installation force of the fastening clip, which may cause failure of the rail fastening system.